Does FDI Impact Carbon Dioxide Emissions? - Kusumawardani, Deni; Umami, Siti Nur; Ulima, Ananda Olga (International Journal of Psychosocial Rehabilitation, 2020)
Foreign Direct Investment (FDI) is an important factor to bust economic development and stimulate economic growth. Rapid economic growth has an impact on environmental degradation. This study aims to determine the direct, indirect, and total effects of FDI on CO2 emissions based on GNI (Gross National Income), categorized as low-income countries, lower-middle income countries, upper-middle income countries, high income countries and global panel. This research uses General Method Moment (GMM) with three least square (3SLS) GMM approach. The data used in this research is retrieved from the World Development Indicator World Bank for period 1998-2014. The estimation results conclude there is a positive direct effect of FDI on CO2 emissions for lower-middle and upper- middle income countries, but not significant for low-income, high-income countries, and global panel. FDI has a significant positive indirect effect across all groups of countries and significant positive total effect across groups.